PROBLEMATIKA PEMBELAJARAN STATISTIKA PADA JURUSAN SOSIAL KEAGAMAAN KRISTEN - Jean Ilela (IAKN Ambon, 2019)
The role of meaningful statistics is of increasing importance in today's world filled with data. Quoting the slogan of the Central Bureau of Statistics which carries the slogan